2023
DOI: 10.3847/1538-4357/ace8fe
|View full text |Cite
|
Sign up to set email alerts
|

NY Bootes: An Active Deep and Low-mass-ratio Contact Binary with a Cool Companion in a Hierarchical Triple System

Fangbin Meng,
Liying Zhu,
Shengbang Qian
et al.

Abstract: The first detailed photometric and spectroscopic study of G-type short-period binary NY Boo is presented. The radial velocity curve was obtained by the cross-correlation function (CCF) method based on LAMOST and SDSS spectra, which derived its mass ratio as q = 0.139(1/7.2). The CCF profiles of the SDSS spectra clearly show the existence of a cool third component, which is supported by the results of the orbital period investigation. The period study based on the O-C analysis indicates that besides a long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…the rate of mass transfer for V0405 Dra is determined to be dM 2 /dt = −6.27(±0.06) × 10 −7 M e year −1 . This rate is significantly higher compared to other DLMRCBs (Li et al 2022;Meng et al 2023), suggesting that the fast decreases in the orbital period might result from a combination of mass transfer and angular momentum loss due to the tertiary body. Given the accelerated period decrease, V0405 Dra is likely to evolve toward a more closely contracted configuration, potentially culminating as an FK Com-type star.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…the rate of mass transfer for V0405 Dra is determined to be dM 2 /dt = −6.27(±0.06) × 10 −7 M e year −1 . This rate is significantly higher compared to other DLMRCBs (Li et al 2022;Meng et al 2023), suggesting that the fast decreases in the orbital period might result from a combination of mass transfer and angular momentum loss due to the tertiary body. Given the accelerated period decrease, V0405 Dra is likely to evolve toward a more closely contracted configuration, potentially culminating as an FK Com-type star.…”
Section: Discussionmentioning
confidence: 69%
“…They could offer an excellent opportunity to study scenarios of stellar mergers (Stepien 2006). By examining the long-term period changes in DLMRCBs, Qian et al (2006) proposed two potential evolutionary scenarios by which DLMRCBs can evolve into Blue Straggler/FK Com-type stars: systems with a decreasing period will experience a contraction of the inner and outer critical Roche lobes, and this contraction would enhance the degree of contact configuration; once the photospheric surface reaches the outer critical lobe, these systems will merge rapidly due to dynamic instability (Meng et al 2023). While systems with an increasing period are undergoing the mass transfer from the less massive component to the more massive one, such a process could result in the decrease of mass ratio and the increase of J spin /J orb .…”
Section: Introductionmentioning
confidence: 99%
“…In order to clearly define the two possible causes, one should search for additional evidence of magnetic activity (e.g., periodic effects in some emission lines as activity indicators or cyclic effects in long-term photometry) or third-body effects (e.g., a third spectrum in high-resolution spectroscopy or periodic changes of the γ velocity). For instance, using infrared spectra, Meng et al (2023) confirmed a cool tertiary component for the NY Boo system. From the longterm photometry, Hu et al (2020) provided strong evidence of cyclic magnetic activity for the near-contact binary V0599 Aur.…”
Section: Notesmentioning
confidence: 98%
“…Because the component stars of contact binaries undergo rapid rotation with deep convective zones, the O'Connell effect is, in general, associated with stellar activity (Sriram et al 2017). For some contact binaries, the O'Connell effect is almost stable, while in other systems, it follows an irregular (Balaji et al 2015;Sriram et al 2017) or quasiperiodic variation (Meng et al 2023;Yılmaz et al 2023), even accompanied by an anticorrelation variation between the primary and secondary eclipse times (Tran et al 2013). Usually, the quasi-periodic and anticorrelated variations, which are often dominated by a period of 50-200 days in short-period eclipsing binaries, can be attributed to the surface differential rotation, leading to longitudinal spot migration (Kalimeris et al 2002;Tran et al 2013).…”
Section: Introductionmentioning
confidence: 99%